염증성 피부질환 개선 기능 소재로서 둥근전복(Haliotis discus) 유래 항균펩타이드 Ab4-7의 항염증 효과 - 최수철; Soo-cheol Choi; 서정길; Jung-kil Seo; 황준호; Joon-ho Hwang; 이기영; Ki-young Lee; 이인아; In-ah Lee (大韓化粧品學會誌, 2020)
서해안에 서식하는 해양생물인 전복은 항산화 및 항염증 효과가 있으며, 항생제 개발 및 화장품 원료 등 다양한 산업에 활용될 수 있는 잠재력을 가진 자원이다. 본 연구에서 우리는 서해안의 다양한 해양 생물중에서 전복을 선택하였으며, 전복에서 분리한 항균펩타이드(AMP)를 이용하여 항균펩타이드 유도체인 Ab4-7를 규명하고 생리활성을 연구하였다. Ab4-7의 항염증 효능을 확인하기 위해 염증이 유도된 RAW 264.7에 Ab4-7을 처리한 결과, 염증성 사이토카인, TLR4, TNF-α, IL-1β, COX-2, iNOS 등을 억제하고 항산화와 관련된 유전인자인 HO-1의 mRNA 발현을 증가시켰다. Ab4-7의 강력한 항산화 및 항염증 효과를 바탕으로, 염증이 유도된 RAW 264.7 세포에서 Ab4-7이 extrocellular matrix metalloproteinase (ECM) 분해에 관여하여 다양한 염증성 피부질환을 유도하는 유전자인 matrix metalloproteinase (MMPs)를 조절하는 효과를 RT-PCR을 통해 확인하였다. Ab4-7은 강력한 항염증 및 항산화 효과를 가지고 있으며, 항염증 및 항산화 효과를 통한 MMPs 관련 유전인자 조절을 통해 다양한 염증성 피부질환 치료제의 기능성 재료로 활용될 수 있다고 사료된다. Abalone, a marine organism inhabiting the west coast of Korea, has antioxidant and anti-inflammatory effects, and is a resource with potential to be used in various industries such as antibiotic development and cosmetic raw materials. In this study, we chose abalone among various marine lives on the west coast. Antibacterial peptide (AMP) was separated from abalone and its derivative Ab4-7 was identified and its physiological activity was studied. The treatment of Ab4-7 in inflammatory RAW 264.7 to check the anti-inflammatory efficacy nhibited inflammatory cytokines, TLR4, TNF-α, IL-1β, COX-2, and iNOS and increased mRNA manifestation of HO-1, genes related to antioxidants. Based on the strong antioxidant and anti-inflammatory effects of Ab4-7, the effects of Ab4-7 in the inflammatory RAW 264.7 cells were identified through RT-PCR, which regulates the gene Matrix Metalloproteinase (MMPs) that induces a variety of inflammatory skin diseases by engaging in the decomposition of the extrocellular matrix metalloproteinase (ECM). Taken together, it is concluded that Ab4-7 has a powerful anti-inflammatory and antioxidant effect and can be used as a functional material for various inflammatory skin disease treatments by controlling the genes associated with matrix metalloproteinase (MMPs).